Discovery of Obesoconnus Jałoszyński in the Oriental Region (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2023)
To date, Obesoconnus Jałoszyński is known to occur in French Guiana, Mexico and Costa Rica. Here, two new species, O. asymmetricus sp. n. and O. pallidus sp. n., are reported to occur in Thailand. Scydmaenine genera showing a similar distribution are discussed, and since the ‘Alloraphes/Stenichnodes group’, to which Obesoconnus belongs, is known to occur in Neotropical, Afrotropical and Oriental regions, it is possible that in the future the genus may be discovered also in tropical Africa.